Case Report: Isolated and Focal Non-necrotizing Granulomatous Inflammation of Mitral Valves: A Report of Two Cases - Pichler Sekulic, Simona; Sekulic, Miroslav (Frontiers in Cardiovascular Medicine, 2021)
Cardiac valve inflammation is seen in the setting of autoimmune or infectious processes, and rarely is valvulitis characterized by granulomatous inflammation. We present two patients who underwent surgical repair of prolapsing/regurgitating mitral valves. Excised valve tissue in both cases revealed commonly encountered nodular fibrosis and calcification, however each also revealed an isolated focus of non-necrotizing granulomatous inflammation. Typical implicating etiologies for non-necrotizing granulomatous inflammation were not present for either patient based on clinical history, or radiologic and laboratory data. In a review of 1048 cardiac valves excised at our institution, the finding of non-necrotizing granulomatous inflammation was seen in only the two described cases (prevalence of 0.19%). The description of non-necrotizing granulomatous inflammation within cardiac valves is limited in the literature, and the significance of the detailed isolated and incidental finding is unclear and requiring further investigation.